Odpowiedzi

2010-02-25T20:33:48+01:00
A) (a+2)h dla a = 7 i h = 1/3
(7+2)*1/3=9*1/3=3
B) 4x/y(x+y) dla x = 6 i y = -2
4*6/-2(6-2)=24/-2*4=24/-8=-3
C) -x + 2y -3 dla x = -5 i y = -4
-(-5)+2*(-4)-3=5-8-3=-6


a) 2x+1 dla x=-4
2(-4)+1=-8+1=-7
b) 2x+1 dla x=0
2*0+1=0+1=1
c) 2x+1 dla x=1 1/2
2*3/2+1=3+1=4
d) 2x+1 dla x=-2/3
2(-2/3)+1=-4/3+1=-1/3
2010-02-25T20:35:45+01:00
Oblicz wartość liczbową wyrażenia
A) (a+2)h dla a = 7 i h = 1/3
(7+2)1/3=9*1/3=3

B) 4x/y(x+y) dla x = 6 i y = -2
4*6/-2(6-2)=24/-8=-3

C) -x + 2y -3
dla x = -5 i y = -4
5-8-3=-6

Oblicz wartość wyrażenia 2x + 1 dla:
a) x = -4
2*(-4)+1=-7

b) x = 0
2*0+1=1

c) x =1 1/2
2*(3/2)+1=4

d) x = - 2/3
2*(-2/3)+1=-1/3
2010-02-25T20:37:16+01:00
1 a)
(7+2)×1/3=9×1/3=9/3=3
b) 4×6:(-2)=24:(-2)=(-12)
c) -(-5)+2×(-4)-3=5+2×(-4)-3=5+9-8)-3=-6

2.
a) 2×9-4)+1=(-8)+1=(-7)
b) 2×0+1=0+1=1
c) 2×1,5+1=3+1=4
d) 2×(-2/3) +1=(-4/3)+1=(-1/3)